2017
DOI: 10.1186/s12891-017-1563-8
|View full text |Cite|
|
Sign up to set email alerts
|

Association between antibodies to carbamylated proteins and subclinical atherosclerosis in rheumatoid arthritis patients

Abstract: BackgroundRheumatoid arthritis (RA) patients carry a high risk of cardiovascular morbidity and mortality. The excess of cardiovascular disease cannot be entirely explained by traditional risk factors and the immune system contributes to the development of atherosclerosis. Moreover, post-translational modifications such as citrullination and carbamylation have been linked to inflammation and atherosclerosis. Anti-carbamylated proteins antibodies (anti-CarP) are a new subset of autoantibodies identified in RA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 45 publications
2
31
0
1
Order By: Relevance
“…Similarly, Brink et al reported a more severe radiographic damage in 42.2% of RA patients positive for such antibodies over 2 years [46]. Anti-CarP antibodies have been also correlated with subclinical atherosclerosis and mortality in RA patients [47,48]. In the study by Spinelli et al, the association between anti-CarP antibodies and measures of endothelial dysfunction, used as markers of subclinical atherosclerosis, was described in 50 RA patients [47].…”
Section: Anti-mentioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, Brink et al reported a more severe radiographic damage in 42.2% of RA patients positive for such antibodies over 2 years [46]. Anti-CarP antibodies have been also correlated with subclinical atherosclerosis and mortality in RA patients [47,48]. In the study by Spinelli et al, the association between anti-CarP antibodies and measures of endothelial dysfunction, used as markers of subclinical atherosclerosis, was described in 50 RA patients [47].…”
Section: Anti-mentioning
confidence: 89%
“…To date, efforts should be pointed out to harmonize and standardize biomarkers detection in order to allow comparison and generalization of results either at a research level, and in the everyday clinical setting. observational studies were retrieved and included in the review [44][45][46][47][48].…”
Section: Response To Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…These antibodies were recently identified in rheumatoid arthritis patients and were associated with subclinical cardiovascular disease 6263. In addition, carbamylation has been shown to be pro-atherogenic in other disease states 64.…”
Section: Mechanisms Linking Rheumatoid Arthritis and Cardiovascular Dmentioning
confidence: 99%
“…Anti-CarP Ab is a risk factor for future joint destruction independent of ACPA [1,[33][34][35][36][37]. A previous study reported that the anti-carbamylated albumin antibody was associated with a history of cardiovascular disease (CVD) [15] and anti-CarP Ab was associated with multiple indices of arteriosclerosis [38]. The intensity of treatment and screening plans for CVD may be modulated in accordance with the antibody profile.…”
Section: Other Possibilities For Anti-carp Ab In Clinical Settingsmentioning
confidence: 99%